2018
DOI: 10.3233/jad-180280
|View full text |Cite
|
Sign up to set email alerts
|

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment

Abstract: The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 81 publications
6
28
1
Order By: Relevance
“…This finding has also been echoed in another local study, which found an association between WMH and MTA among patients with clinically diagnosed amnestic deficits [14]. We have also previously demonstrated that regional WMH is associated with greater grey matter atrophy in patients with mild cognitive impairment [36]. The present study suggests the direct effect of CVD on clinical symptoms of AD and MTA, in the absence of amyloid pathology.…”
Section: Discussionsupporting
confidence: 87%
“…This finding has also been echoed in another local study, which found an association between WMH and MTA among patients with clinically diagnosed amnestic deficits [14]. We have also previously demonstrated that regional WMH is associated with greater grey matter atrophy in patients with mild cognitive impairment [36]. The present study suggests the direct effect of CVD on clinical symptoms of AD and MTA, in the absence of amyloid pathology.…”
Section: Discussionsupporting
confidence: 87%
“…The nding of widespread negative association between WMH load and GMV at both the voxel-wise and ROI level at high WMH load evidenced in our study is supported by numerous prior studies (11,(15)(16)(17)(18)(19)(20)(21)(22)26). However, the mechanisms underlying this relationship need to be examined further.…”
Section: Discussionsupporting
confidence: 88%
“…This relationship thus needs further elucidation in early disease stages. While our previous work has also shown that derogatory in uences of WMH on GMV are most widespread at the MCI stage, compared to both cognitively normal and AD stages (26), the possible differential effects of WMH load on GMV in the cognitively normal and MCI remain to be elucidated.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations